Impact of Age and Sex on Anatomical Variations of the Infra-acetabular Screw Corridor: An Imaging Study - Wang, Lei; Zhang, Yu; Yin, Guoyong; Lu, Chun (Clinics in orthopedic surgery, 2025)
Background: This study investigates how age and sex influence the morphology of the infra-acetabular screw (IAS) corridor by examining its anatomical features and relationships with adjacent critical structures across diverse age and sex cohorts. Additionally, surgical simulations were performed to identify reliable anatomical landmarks and refine intraoperative fluoroscopic images. Methods: A retrospective analysis (2016–2024) was performed on 178 unilateral acetabular fracture cases (105 males, 73 females; mean age, 55.74 ± 15.0 years). Participants were stratified into 4 groups based on sex and age (threshold: 60 years): young males (n = 57), elderly males (n = 48), young females (n = 36), and elderly females (n = 37). Pelvic models were reconstructed using Mimics 21.0 software to measure infra-acetabular corridor diameter (IACD) and obturator groove depth (OGD). IAS placement was simulated to determine the entry point, screw dimensions, and minimum distances to adjacent structures. Simulated fluoroscopic images assessed the sensitivity and specificity for cortical breach detection at incremental screw diameters. Results: Young males demonstrated marginally greater distances to the eminentia iliopectinea compared to elderly males (13.04 ± 1.86 vs. 12.32 ± 1.20 mm, p < 0.05). Elderly females had a significantly larger IACD than young females (4.98 ± 0.95 vs. 4.51 ± 0.58 mm, p < 0.05), and female OGD exceeded that of males (11.16 ± 2.10 vs. 9.66 ± 1.98 mm, p < 0.05). A strong negative correlation was identified between IACD and OGD (r = 0.842): IACD = 8.730−0.358 OGD. The modified iliac-outlet view reduced false positives from 76.4% to 44.38% and improved sensitivity. Conclusions: The IAS entry point should be more medial in young males than in elderly males. Elderly females exhibited a larger IACD. The negative correlation between IACD and OGD results in a narrower IACD in females. The modified iliac-outlet view improved sensitivity and reduced false positives for cortical breach detection. KCI Citation Count: 0